Pengetahuan Ibu tentang Imunisasi pada Bayi - Hartaty Hartaty; Maria Kurni Menga (Sarana Ilmu Indonesia (salnesia), 2019)
Immunization is giving the body immunity to a disease by putting something in the body so that the body is resistant to diseases that are endemic or dangerous to someone. Immunization comes from the word immune, which means immune or resistant. This needs special attention from health workers because with a good level of knowledge will help reduce mortality in infants not being immunized. Purpose of this research was to know the description of your mother's level of knowledge about infant immunization. Researchers used descriptive research. The sampling technique uses the accidental sampling method where the sample is all those who happen to come to work at the Batua Makassar Public Health Center at the time of the study. The method of collecting data is based on the willingness of the subjekts by filling out statements and signing the consent form to be subjekts and filling in the questionnaire based on the time and place agreed by the subjekts then presented in the data tabulation. This research showed that of 40 subjekts, 25 subjekts (62.5%) had sufficient knowledge in the category, 8 subjekts (20%) had knowledge in the good category and 7 subjekts (17.5%) in the knowledge category were lacking. Therefore, the important role of nurses to do promotive and preventive efforts on matters relating to immunization programs for infants and can provide more information to the public so that people know more about immunization.